Single‐Molecule Magnetism in a Single‐Ion Triamidoamine Uranium(V) Terminal Mono‐Oxo Complex1. Issue 18 (8th April 2013) - King, David M.; Tuna, Floriana; McMaster, Jonathan; Lewis, William; Blake, Alexander J.; McInnes, Eric J. L.; Liddle, Stephen T.
<x xml:space="preserve">Abstract</x> Single‐molecule magnets: Straightforward oxidation of a triamidoamine uranium(III) complex with trimethyl‐N‐oxide affords a uranium(V) terminal mono‐oxo complex which is the first clear‐cut example of a uranium(V) single‐molecule magnet (SMM). This monometallic complex unambiguously shows that a strongly axially ligated and thus anisotropic ligand field can be used to overcome the limited magnetic anisotropy of uranium(V).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>